Student Perceptions of PIESQ Management 3.0 Training at the Universitas PGRI Semarang - Sri Suciati; Arri Handayani; Dyah Nugrahani; Siti Musarokah; Yuli Kurniati Werdaningsih (International Journal of Research in Education, 2022)
The study aims to find the right PIESQ Training material model to fit the demands of the time while adhering to the Universitas PGRI Semarang’s identity. The goal of the first year is to identify the perception and impact of training on the quality of student’s Physic, Intellectual, Emotional, and Spiritual (PIES). To achieve its goal, the study employs a research and development approach (Research and Development - R & D). The study will be held at the University of PGRI Semarang with a population of all students of the Universitas PGRI Semarang who have participated in the PIESQ Training and the sample was taken purposive sampling. Overall, students' impressions of the PIESQ Management 3.0 training were positive, according to data analysis results. Despite the small sample size, a few people have complained that the training itself is tedious and boring. There were still a few respondents who said that the materials were out of date.